A genome-wide scan of positive selection signature using Ovine Infinium® HD SNP BeadChip in two Romney lines, selected for resistance or resilience to nematodes - Yan J; Dukkipati VSR; Blair HT; Biggs PJ; Hamie JC; Greer A (Massey University)
A study was undertaken to identify selection signatures associated with resistance to gastrointestinal nematodiasis in sheep. Ninety-three Romney sheep from two selection lines (resistant or resilient) were genotyped using the Ovine Infinium® HD SNP BeadChip, and extended haplotype homozygosity (EHH) and site-specific extended haplotype homozygosity (EHHS) analyses were undertaken. In total, 224 SNPs (147 in EHH and 77 in EHHS) were found to be significant (p <0.0001). Preliminary exploration of 10 SNPs found them to be located within two previously identified QTLs, namely LATRICH_2 and FECGEN, which were associated with nematode larval count and faecal egg count, respectively.